FREQUENCY OF NUTRITIONAL ISSUES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (The Research of Medical Science Review, 2025)
Background: Many Type 2 Diabetes Mellitus (T2DM) patients suffer from nutritional deficiency which affect the management of diabetes and their general health status. Metabolic disturbances together with impaired insulin sensitivity and complications become worse due to deficiencies of vitamins and minerals. Improving patient care and glycemic control becomes necessary after identifying these deficiencies. Objectives: An investigation of nutritional issues that affect t2dm patients together with their diabetes management outcomes. Study design: A cross-sectional study. Place and duration of study. From 10 September 2024 to 9 March 2025 Medicine Department, Sandeman Provincial Hospital / Bolan Medical Complex Hospital Quetta. Methods: A study analysis employed a cross-sectional methodology to study 129 patients who had T2DM. Blood tests measured the nutritional condition of patients by examining essential vitamins and minerals. The study collected vital data concerning patient demographics and treatment medications as well as existing health conditions. chi-square and t-tests performed the statistical assessments for comparing deficiency rates. Results: A sample of 129 patients with Type 2 Diabetes participated in the study while the subjects averaged 56.4 years (SD = 9.2). Vitamin D deficiency affected 60% of patients and 30% had low B12 while 35% demonstrated magnesium deficiency in the study group. An analysis revealed that the p-value of lesser than 0.05 demonstrated statistical significance for the relationship between diabetes control and vitamin deficiencies.